Data Visualization and Analysis in Second Language Research - Sun, Yiou; Wang, Ping (Frontiers in Psychology, 2022)
I am working as both a TEFL teacher and an SLA researcher in China, doing SLA research. Recently, I have been working on new approaches to data analysis and I've found that a book titled 'Data Visualization and Analysis in Second Language Research' by Dr. Guilherme D. Garcia is of great significance in empirical research in the field of SLA. This book serves only as a practical and user-friendly guide to beginners involved in SLA research, but also navigation to veteran SLA researchers devoted to new perspectives in data analysis. So far, the author has made his first attempt to connect data visualization under R to SLA research. The author reviews the previous research results and suggests some modifications through running R. From my perspective, it fills a gap in the SLA research practice - to lead readers into a new track of visualizing their reported results. Overall, to make an increasingly higher demand for SLA research, this book is particularly designated for quantitative data analysis in SLA. It is strongly recommended to write a book review to introduce readers to the realm of data visualization and help most SLA researchers better understand the potential value of R and visualization in SLA research.